Le projet « On our own together II » : à l’aube d’une ère nouvelle: The « On our own together II » project: at the dawn of a new era - Davidson, Ann-Louise; Leblanc, Raymond; Leno, Silas; Clément, Nathalie; Godbout, Sophie; Moldoveannu, Mirela; Payeur, Yolaine; Turcotte, Catherine (Revue francophone de la déficience intellectuelle, 2004)
Dans le cadre d’un projet visant le processus de transition de la vie dans leur famille à la vie dans la communauté d’adultes vivant avec une déficience intellectuelle, sept doctorants ont participé à une recherche-action. Plus spécifiquement, ce projet visait à accompagner pendant deux mois quatorze adultes déficients dans leur vie commune dans une résidence universitaire. Ce texte s’attache à faire la narration de l’expérience vécue par les jeunes adultes, telle que représentée par le groupe de doctorants. Il présente l’entrée dans le projet, une analyse serrée des problématiques à l’étude et une synthèse de l’expérience sous forme d’implications pour le suivi du projet. Abstract In the context of a community insertion and housing project for adults living with intellectual disabilities, which was hosted at a local University residence in May and June 2004, seven doctoral students participated in an action-research. The purpose of the study was to provide fourteen young adults the opportunity to experience living away from parents for two months to see what it’s like. Four specific issues, the everyday problem solving, the overconfident personnality, telephone use, and television viewing, were targeted by the researchers for this project. This paper reconstructs a narration of the experience lived, by providing an analysis of the specific targeted issues, and a synthesis of the experience which provides implications for a follow-up on the project.